The Biology and Therapeutic Implications of Tumor Dormancy and Reactivation - Yadav, Amit S.; Pandey, Poonam R.; Butti, Ramesh; Radharani, N. N. V.; Roy, Shamayita; Bhalara, Shaileshkumar R.; Gorain, Mahadeo; Kundu, Gopal C.; Kumar, Dhiraj (Frontiers in Oncology, 2018)
Advancements in the early detection of cancer coupled with improved surgery, radiotherapy and adjuvant therapy led to substantial increase in patient survival. Nevertheless, cancer metastasis is the leading cause of death in several cancer patients. The majority of these deaths are associated with metastatic relapse kinetics after a variable period of clinical remission. Most of the cancer recurrences are thought to be associated with the reactivation of dormant disseminated tumor cells (DTCs). In this review, we have summarized the cellular and molecular mechanisms related to disseminated tumor cells and the role of microenvironmental niche. These mechanisms regulate the dormant state and help in the reactivation which leads to metastatic outgrowth. Identification of novel therapeutic targets to eliminate these dormant tumor cells will be highly useful in controlling the metastatic relapse-related death with several cancers.